Development of QR Code Based Archipelago Insight Media to Improve Students’ Conceptual Understanding - Abdul Haris Subarjo; Nurcahyani Dewi Retnowati; Himawan Putranta (Lembaga Ketahanan Nasional Republik Indonesia, 2025)
Purpose: his study aims to develop and examine the feasibility and readability of QR Code-based Archipelago Insight lecture media for citizenship education lectures at the university level. Study Design/Methodology/Approach: This research employed a research and development approach using the 4D model, consisting of the define, design, develop, and disseminate stages. The media were developed by organising Archipelago Insight materials into three main QR Code-based menus: meaning of words, definitions, and history. The developed product was assessed through feasibility testing by six validators and practitioners, consisting of two Archipelago Insight content experts, two civic education learning media experts, and two practitioners. A readability test was also conducted with 100 students as direct users of the media. Findings: The feasibility assessment showed that the QR Code-based Archipelago Insight lecture media obtained an average score of 4.12, which was included in the feasible category. The highest feasibility score was found in the suitability of material with the media, while the lowest score was found in the clarity of material, although it remained within the feasible category. The student readability test obtained an average score of 3.63, which was included in the very feasible category. These findings indicate that the developed media are suitable, readable, and practical for use as an alternative medium in citizenship education lectures. Originality/Value: This study offers QR Code-based Archipelago Insight lecture media as a practical digital alternative for presenting broad civic education materials. It also provides an initial basis for further studies on the role of QR Code-based media in supporting Archipelago Insight learning in blended and distance lecture contexts.